Advantages, applications, and future directions of in vivo aptamer SELEX: A review - Minchuan Lyu; Chi Ho Chan; Ziqi Chen; Yumeng Liu; Yuanyuan Yu (Molecular Therapy: Nucleic Acids)
In vivo systematic evolution of ligands by exponential enrichment (SELEX) emerged as a transformative technique for directly identifying aptamers within living organisms. Unlike traditional in vitro methods that often fail to capture the complexity of biological interactions in physiological environments, in vivo SELEX leverages whole living organisms as selection targets. This strategy significantly enhances the specificity, functionality, and physiological relevance of the selected aptamers, making them more viable for therapeutic, diagnostic, and imaging applications. The aim of this review is to elucidate the unique advantages of in vivo SELEX compared to conventional in vitro techniques. It focuses on how in vivo SELEX improves aptamer specificity, physiological relevance, and pharmacokinetic properties, thereby enhancing their potential for use in diagnostics and therapeutics. This review highlights the principles, advancements, and challenges of in vivo SELEX, while discussing its potential to bridge the gap between aptamer discovery and clinical translation. By enabling the selection of aptamers under real physiological conditions, in vivo SELEX addresses critical limitations of in vitro methods, such as off-target effects and poor clinical translatability. The review also explores the applications of in vivo SELEX in various fields, including neurology, oncology, and cardiovascular diseases, and provides insights into future directions for optimizing this technology.